MOTIVASI BELAJAR ANAK BERKEBUTUHAN KHUSUS (ABK) KESULITAN BELAJAR DAN KLASIFIKASI SLOW LEARNING - Peronica Tamba; Ananda Kurniawan; Muhammad Iqbal; Opi Andriani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the learning motivation of children with special needs (ABK) who have learning difficulties and the classification of slow learning. The methods used are interviews, observation and documentation, then the data will be analyzed using descriptive qualitative methods. Children with special needs are children who have their own unique types and characteristics, which differentiate them from normal children in general. This situation demands an understanding of the nature of children with special needs (ABK). Learning motivation is all the driving force and direction for someone to do something with the aim of increasing the individual's own knowledge and experience. Student learning success can be determined from the motivation that the student has. Students who have high motivation in learning will definitely tend to have higher learning outcomes, conversely if the student's learning motivation is low then the student's learning outcomes will also be low. Motivation really influences students' learning outcomes, that's why many students have low learning outcomes due to their lack of motivation. When students have motivation in learning, they can improve their academic abilities and can influence learning outcomes, as well as Children with Special Needs (ABK) who also have academic abilities that can be developed in order to improve learning outcomes. With motivation it will certainly provide enthusiasm and encourage children to develop their academic abilities. The difficulties experienced by children with special needs (ABK) can of course be overcome with the help of teachers who are experts in their fields and the facilities and infrastructure available at school, so that they can improve their abilities just like children in general.